Incentives to retire later : a solution to the social security crisis? - Friedrich Breyer; Mathias Kifmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
As one possible solution to the well-known financing crisis of unfunded social security systems, an increase in the retirement age is a popular option. To induce workers to retire later, it has been proposed to strengthen the link between retirement age and benefit level. The present paper is devoted to analyzing the long-run financial implications of such a reform. We show that with actuarial adjustments the long-run contribution rate is an increasing function of the retirement age chosen by workers. Moreover, the implicit tax paid to the pension system by a participant can increase in the long run if the retirement age rises in response to a "steep" adjustment rule. In this sense, the proposed "cure" may worsen the disease. Finally, we propose an alternative adjustment scheme which avoids these negative consequences. Finally, we show how the negative effects can be avoided by forming a capital stock from the additional revenues due to later retirement. – – Als ein möglicher Ausweg aus der drohenden Finanzkrise umlagefinanzierter Rentensysteme wird gegenwärtig eine Anhebung des Rentenzugangsalters von vielen favorisiert. Um allerdings Arbeitnehmern einen Anreiz zur Verlängerung der Lebensarbeitszeit zu geben, muss nach Auffassung der meisten Experten die Beziehung zwischen Beiträgen und Rentenansprüchen gestärkt werden. In dieser Arbeit werden die langfristigen finanziellen Konsequenzen einer solchen Reform analysiert. Wir zeigen, dass bei versicherungsmathematischen Zuschlägen für Mehrarbeit der Beitragssatz langfristig eine steigende Funktion des tatsächlich gewählten Rentenalters ist. Darüber hinaus steigt auch die implizite Steuer, die ein repräsentativer Versicherter an die Rentenkasse zahlt, sofern das Rentenalter in Folge einer ,,steilen" Zuschlagsfunktion zunimmt. In diesem Sinne könnte die vorgeschlagene "Behandlung" die diagnostizierte "Krankheit" verschlimmern. Abschließend zeigen wir, wie der negative Effekt durch Aufbau eines Kapitalstocks vermieden werden kann.
Keywords: H55; J18; 330; Umlageverfahren; Rentenzugangsalter; versicherungsmathematische Zuschläge; Pay-as-you-go; retirement age; actuarial adjustment; Altersgrenze; Arbeitsangebot; Ökonomischer Anreiz; Gesetzliche Rentenversicherung; Umlageverfahren; Äquivalenzprinzip; Theorie; Deutschland